Role of intestinal probiotics in the modulation of lipid metabolism: implications for therapeutic treatments - Xiaoran Song; Yanan Liu; Xin Zhang; Peifang Weng; Ruilin Zhang; Zufang Wu (Food Science and Human Wellness)
Currently, accumulating pieces of evidence indicate that probiotics, living in the gastrointestinal tract, play an important role in regulating host metabolism. As a tool, probiotics have great potential for treating lipid metabolism diseases. However, the relationship between probiotics and abnormal lipid metabolism is still unclear, and the mechanism of action has been become a focus of microbiome research. Therefore, taking intestinal probiotics as the starting point, this article combs the relationship between probiotics and lipid metabolism. Moreover, we discuss the underlying mechanisms of intestinal probiotics regulating lipid metabolism and summarize the therapeutic strategies for abnormal lipids metabolism. This article provides a reference for the further utilization of probiotics in the field of functional foods (food industry). Meanwhile, it will benefit the clinical diagnosis and treatment of lipid metabolism diseases.